Characterizing HLA-A2-restricted CD8+ T-cell epitopes and immune responses to Omicron variants in SARS-CoV-2-inactivated vaccine recipients - Xiao, Chanchan; Xiang, Jian; Wang, Haoyun; Gao, Wen; Peng, Tianchan; Li, Shumin; Su, Jun; Chen, Xi; Gao, Lijuan; Shi, Ruohu; Mou, Xinyi; Yuan, Jun; et al. (Frontiers in Immunology, 2025)
IntroductionRecent surveillance has identified the emergence of the SARS-CoV-2 Omicron ariant, which exhibits the ability to evade multiple neutralizing antibodies generated by prior infection or vaccination. However, significant knowledge gaps remain regarding the CD8 T-cell immune reactivity to the Omicron variant. This study aims to evaluate the characteristics of HLA-A2-restricted CD8 T-cell epitopes from the Omicron variant and analyze epitope-specific CD8 T-cell responses to SARS-CoV-2 inactivated vaccines.MethodsWe conducted a comprehensive analysis of CD8 T-cell responses to SARS-CoV-2 inactivated vaccines, focusing on HLA-A2-restricted epitopes derived from the Omicron variant. Mutant epitopes were evaluated for their impact on antigen presentation and CD8 T-cell immune reactivity. Additionally, we screened for epitopes that exhibited reduced CD8 T-cell responses following the emergence of the Omicron variant.ResultsOur findings revealed that mutant epitopes in the Omicron variant led to escape from antigen presentation and diminished CD8 T-cell immune responses. We identified two epitopes associated with decreased CD8 T-cell reactivity post-Omicron variant emergence. Notably, we discovered an S protein epitope, 67A>V, which demonstrated similar proportions of CD8 T-cell specificity between the ancestral and mutant strains, suggesting its conservation and potential immunogenicity for vaccine development. Furthermore, the third dose of the inactivated vaccine significantly increased the number of epitope-specific CD8 T cells, underscoring the importance of booster doses in enhancing cellular immune responses against the Omicron variant.DiscussionThis study highlights the ability of the Omicron variant to evade CD8 T-cell immune responses through epitope mutations, while also identifying conserved epitopes with potential utility in vaccine design. The observed increase in epitope-specific CD8 T cells following a booster dose emphasizes the critical role of additional vaccinations in strengthening cellular immunity against emerging SARS-CoV-2 variants. These findings provide valuable insights for the development of next-generation vaccines targeting conserved epitopes and optimizing booster strategies.